Boundedness for a Class of Singular Integral Operators on Both Classical and Product Hardy Spaces - Chaoqiang Tan (Abstract and Applied Analysis)
We found that the classical Calderón-Zygmund singular integral operators are bounded on both the classical Hardy spaces and the product Hardy spaces. The purpose of this paper is to extend this result to a more general class. More precisely, we introduce a class of singular integral operators including the classical Calderón-Zygmund singular integral operators and show that they are bounded on both the classical Hardy spaces and the product Hardy spaces.